2020
DOI: 10.1177/0963689720967672
|View full text |Cite
|
Sign up to set email alerts
|

Glaucocalyxin A Protects H9c2 Cells Against Hypoxia/Reoxygenation-Induced Injury Through the Activation of Akt/Nrf2/HO-1 Pathway

Abstract: Myocardial infarction (MI) is one of the most serious cardiovascular diseases associated with myocardial ischemia/reperfusion (I/R) injury. Glaucocalyxin A (GLA) is a biologically active ent-kauranoid diterpenoid that has been found to ameliorate myocardial I/R injury in mice. However, the mechanism has not been fully investigated. In the present study, we aimed to investigate the effect of GLA on rat cardiomyocytes H9c2 cells exposed to hypoxia/reoxygenation (H/R). The results showed that GLA treatment improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…As an antioxidant, ASIV can activate the Nrf2 signaling pathway and inhibit ROS production (Nie et al, 2019). Upstream of Nrf2, PI3K/Akt is also an important pathway that regulates the cellular defense system to prevent oxidative damage, which is related to Nrf2 activation and HO-1 induction (Peng et al, 2020). Studies have found that blocking the activity of Akt by inhibitors can reduce the protein levels of Nrf2 and HO-1 FIGURE 8 | Inhibitors revealed that ASIV modulate the PI3K/Akt pathway in the myocardium ADR-treated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an antioxidant, ASIV can activate the Nrf2 signaling pathway and inhibit ROS production (Nie et al, 2019). Upstream of Nrf2, PI3K/Akt is also an important pathway that regulates the cellular defense system to prevent oxidative damage, which is related to Nrf2 activation and HO-1 induction (Peng et al, 2020). Studies have found that blocking the activity of Akt by inhibitors can reduce the protein levels of Nrf2 and HO-1 FIGURE 8 | Inhibitors revealed that ASIV modulate the PI3K/Akt pathway in the myocardium ADR-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that not only regulates the phase II detoxification response ( Silva-Palacios et al, 2016 ), but also regulates dominates redox homeostasis and cellular antioxidant defense ( Peng et al, 2020 ). Kelch-like ECH-associated protein 1 (Keap1) is a protein responsible for the cytoplasmic isolation of Nrf2 under physiological conditions ( Kourakis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…HO-1, an intracellular inducible phase II detoxifying enzyme, can be regulated by Nrf2 [213]. The Nrf2/HO-1 signaling pathway is related to defense against a variety of oxidative-inducing agents and represents a promising target for inhibiting MI/RI [213]. Many drugs or extracts thereof, such as resveratrol [211] and triptolide [214], inhibit oxidative stress by activating the Nrf2/HO-1 signal, thereby 9 Oxidative Medicine and Cellular Longevity limiting infarct size and improving cardiac function.…”
Section: Regulation Of the Oxidation Defense Systemmentioning
confidence: 99%
“…After binding to antioxidant response elements (AREs), Nrf2 promotes the expression of antioxidant genes and produces enzymes related to antioxidant defense, such as glutathione reductase (GR), heme oxygenase 1 (HO-1), and superoxide dismutase 1 (SOD1) [ 18 , 209 , 210 , 212 ]. HO-1, an intracellular inducible phase II detoxifying enzyme, can be regulated by Nrf2 [ 213 ]. The Nrf2/HO-1 signaling pathway is related to defense against a variety of oxidative-inducing agents and represents a promising target for inhibiting MI/RI [ 213 ].…”
Section: Interventions Targeting Oxidative Stress and Related Pathways In Myocardial Reperfusionmentioning
confidence: 99%
“…Nrf2 acted an important role in oxidative stress after MI [ 19 ]. Acute exercise stress could improve the level of myocardial antioxidant stress in mice through Nrf2 pathway, while the myocardial tissue of Nrf2 deficient mice presented a high level of oxidative stress [ 20 ]. It was reported that Hydroxysafflor yellow A protected H9C2 cells from apoptosis caused by hypoxia through PI3K/Ak/Nrf2 pathway via upregulating HO-1 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%